Quality of Work Life (QWL) on Professional Care Providers at X Hospital, Jakarta - Fanya Fanya; H. Abdul Kadir; Rokiah Kusumapradja (Journal of Multidisciplinary Academic, 2020)
Productivity is affected by services that will be provided them and influenced in the quality of work life characteristics such as age also years of service on professional care provider themselves. The purpose of the study is conducted at X Hospital to provide empirical evidence in provider influence characteristics and quality of work life (QWL) towards the productivity of professional care providers at hospital X. Here, we used quantitative causality as a research methodology. The professional respondents are a care providers who work in hospital x with survey quantitative. Here, we analyze the data using Structural Equation Modelling with AMOS applications. The results showed the influence of provider characteristics and quality of work life / QWL towards work productivity. The positive effect occurs between the characteristics of the provider with the quality of work life and productivity, but there is a negative influence on the quality of work life on work productivity. Characteristics of the providers at X hospital are dominated by those with high age and long working period. The quality of work life of X hospital is high, with the work productivity of PPA at hospital X showing a moderate value. The findings of this study are the higher age and longer the years of service of professional care providers at X hospital, resulting in a high quality of work life with moderate / normal work productivity